Pengaruh Peran Teman Sebaya, Lingkungan Keuarga, dan Disipin Belajar Terhadap Motivasi Beajar Siswa Jurusan Otomatisasi dan Tata Kelola Perkantoran di SMK Negeri 1 Bawang - Ni'mah, Zulfatun; Ismiyati, Ismiyati (Business and Accounting Education Journal, 2025)
This research aims to examine and analyze the influence of the role of peers, family environment, and learning discipline on students' learning motivation in Office Automation and Management at SMK Negeri 1 Bawang Banjarnegara. This type of research is quantitative research. The population in this study were all Office Automation and Management students at SMK Negeri 1 Bawang Banjarnegara for the 2023/2024 academic year, totaling 324 students including class X, class XI and class XII. The sample in this study was selected using a proportional random sampling technique and calculated using the Slovin formula. From the population, the total sample used was 179 students. The data collection technique used was by distributing questionnaires to respondents. The data analysis used is multiple linear regression analysis and hypothesis testing with the help of SPSS. The results of the research show that the peer role variable (X1) influences students' learning motivation (Y), the family environment variable (X2) influences students' learning motivation (Y), and the learning discipline variable (X3) influences students' learning motivation (Y). Office Automation and Management at SMK Negeri 1 Bawang Banjarnegara.